A Novel Image Data Hiding Scheme with Diamond Encoding. (4th May 2009) - Chao, Ruey-Ming; Wu, Hsien-Chu; Lee, Chih-Chiang; Chu, Yen-Ping
Abstract : A novel data hiding scheme in digital images with the diamond encoding by pixel value adjustment is proposed. The proposed method is the extension of the exploiting modification direction (EMD) embedding scheme. First, the process of embedding partitions the cover image into nonoverlapping blocks of two consecutive pixels and transforms the secret messages to a series ofk -ary digits. For each block, the diamond encoding technique is applied to calculate the diamond characteristic value, and one secretk -ary digit is concealed into the diamond characteristic value. The diamond characteristic value is modified to secret digit and it can be obtained by adjusting pixel values in a block. This scheme is designed in such a way that the distortion of each block after diamond encoding is never out of the embedding parameterk, and the block capacity is equal tolog   2 ( 2 k 2 + 2 k + 1 ) . The diamond encoding provides an easy way to produce a more perceptible result than those yielded by simple least-significant-bit substitution methods. The embedded secret data can be extracted without the original cover image. Experimental results have demonstrated that the proposed method is capable of hiding more secret data while keeping the stego-image quality degradation imperceptible.